Who speaks in cultural creation? Notes on Lucien Goldmann - Frederico, Celso (MATRIZes, 2012)
The matter of the subject in the communicational process is understood by Goldmann according to the theoretical framework derived from his own method – the genetic structuralism. It set him apart from existentialist perspectives (that favor the individual subject), as much as from structuralist ones (that ontologizes the language). The Goldmannian thesis of a trans-individual subject restores the relationships between social life and cultural creation in a very specific framing. Amongst the many texts published by the author, Le dieu caché is which better presents his project for a sociology of culture.